A novel dissolution-precipitation mechanism during liquid phase sintering and its strengthening effects in W-Ni-Fe alloys with low W contents. (August 2022) - Han, Yong; Li, Yuan; Ye, Lei; Du, Zhiyuan; Liu, Zhanggen; Li, Xin; Zhao, Ming-Chun; Atrens, Andrej
Graphical abstract: Highlights: The γ (Fe-Ni, W) phase near the interface was the FeNi3 phase. The interface was a semi-coherent interphase boundary. W atoms continued to mass transfer to the interface area, and W grains formed when the enrichment was sufficient. Ni atoms and Fe atoms in the γ phase lattice were continuously replaced by W atoms during precipitation. The precipitation of ultrafine W grain strengthened the alloy. Abstract: W-Ni-Fe alloys with a low W content are a kind of promising tungsten alloys. However, limited results are available, and the responsible mechanism is not known for their dissolution-precipitation behavior, because long-range migration under the low W concentration is difficult after tungsten dissolution. In this work, a tungsten alloy with a low W content was prepared by liquid phase sintering. A new in-situ dissolution-precipitation process for tungsten alloys with a low W content was identified, which is different from that for tungsten alloys with a high W content. The interface between ultrafine precipitated W grains and the γ(FeNi3, W) phase in tungsten alloys with a low W content was a semi-coherent interphase boundary. Ni atoms and Fe atoms in the γ phase lattice were continuously replaced by W atoms during precipitation. W atoms continued to mass transfer to the interface area, and W grains formed when the enrichment was sufficient. The obtained 50W-25Ni-25Fe tungsten alloy had the superior combination of ultimate tensile strength (UTS) and elongation. The precipitation of ultrafine W grain strengthened the alloy.